Childhood Blood Lead Levels and Adolescent Crime Rates in the United States - Soweh, Jude Juiye (2020)
Juvenile violent crime rates in the United States have been on a continuous decline since 1996. Despite this decrease, youth violence as well as racial differences in crime rates continues to be a public health issue in the United States. Researchers have linked externalization behavior in children to factors including genetics, parental upbringing, abuse, school environment, and media exposure but have not fully considered the relationship between early childhood lead contamination and youth violence. This was an ecologic study of the relationship between early childhood blood lead levels (BLLs; ≥ 10µg/dL before 2012 or ≥ 5µg/dL after 2012) and crime arrest rates in United States. A secondary data analysis was conducted of existing data on youth violence and BLL obtained from the Office of Juvenile Justice and Delinquency Prevention and Center for Disease Control and Prevention respectively. Results of linear multiple regression analysis showed a significant positive correlation between the percentage of confirmed childhood BLL ≥ 10µg/dL in states from 1999 to 2001 and robbery, weapon, and drug abuse arrest rates in 2016. Further analysis indicated that the total crime rate per 100,000 population in states was significantly correlated with the 2012-2016 mean percentage of confirmed childhood BLL ≥ 5µg/dL in states (B = 35.17, p = 0.03). Results may help public health professionals, medical care providers, and policy makers to make informed decisions and better target interventions to further alleviate the effects of childhood lead poisoning at home and abroad. Improvements in children’s health may benefit individuals, families, organizations, and society through the promotion of public health and the reduction of adverse impacts associated with lead contamination in childhood